Strategi Bertumbuh Kepala Madrasah dalam Implementasi E-Rkam Provinsi Kalimantan Timur - Suratman, Suratman; Sugiyono, Sugiyono (el Buhuth: Borneo Journal of Islamic Studies, 2022)
In order to improve the efficiency and effectiveness of BOSNAS budget management, the Ministry of Religion launched a madrasa reform program, one of which was the implementation of the eRKAM application. Various problems and dynamics in the implementation process in the field in each madrasa make it important to study the growth strategy of madrasah principals in implementing eRKAM applications. This type of research is quantitative research, as the data sources are the head of the madrasa, the treasurer of eRKAM, the operator and the madrasa development team. The collection technique was carried out by observation, documentation, interviews and filling out research instruments. The analysis was carried out using the TOWS analysis technique, namely by utilizing internal strengths to take advantage of opportunities and minimize threats from external elements. The results showed that the strategy used by the madrasah principal in implementing eRKAM was a growth strategy, this was based on the results of data analysis using MS Excel which was in coordinates (1.19 on the X axis and 1.73 on the Y axis) located at coordinate 1.